2019
DOI: 10.1111/jicd.12478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biologic implant success parameters in type 2 diabetic glycemic control patients versus healthy patients: A meta‐analysis

Abstract: Aim The aim of the present systematic literature review was to evaluate bleeding on probing (BOP), pocket depth (PD), and marginal bone loss (MBL) in type 2 diabetes mellitus (T2DM) control patients. Methods An electronic literature search was conducted through PubMed, Web of Science, Cochrane, Embase, and ScienceDirect. The search included prospective human clinical studies that analyzed the success of dental implants in T2DM control patients. For inclusion, studies should have had a minimum of 1‐year follow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Thus, edentulism becomes one of the main consequences for these patients [ 6 , 8 ]. Diabetic patients with uncontrolled glycemia have been shown to have worse results than those of controlled DM2 and nondiabetic patients, such as a higher incidence of implant failure [ 21 , 32 ]. In addition to the fact that the disease is characterized by microvascular complications, tissue damage, and a higher risk of infection, these factors greatly influence dental treatment [ 5 , 8 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, edentulism becomes one of the main consequences for these patients [ 6 , 8 ]. Diabetic patients with uncontrolled glycemia have been shown to have worse results than those of controlled DM2 and nondiabetic patients, such as a higher incidence of implant failure [ 21 , 32 ]. In addition to the fact that the disease is characterized by microvascular complications, tissue damage, and a higher risk of infection, these factors greatly influence dental treatment [ 5 , 8 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between elevated HbA1c levels and increased marginal bone loss had a statistically significant result in a different prospective study by Aguilar-Salvatierra et al [16]. However, in a recent meta-analysis of seven prospective studies [17], Lagunov et al observed that PD, BOP, and marginal bone loss showed a significantly higher increase in type 2 DM patients as compared to healthy patients, after a period of 12 months, independently from the level of glycemic control.…”
Section: Discussionmentioning
confidence: 96%
“…Several factors would influence the bone remodeling around dental implants, including the blood glucose and physical illnesses of patients, the position of fixture and the major surface treatment of the implants [10]. The marginal bone loss (MBL) in diabetes patients is greater than that in nondiabetic individuals, regardless of whether the former group is glycemic controlled [11]. The higher MBL in T2DM patients could show the impaired bone condition around implants.…”
Section: Introductionmentioning
confidence: 99%